Enhancing Excellence: Analyzing Quality Management in Islamic Boarding Schools - Ismail, Feiby; Santoso, Agung Budi; Umar, Mardan; Halim, Audrey Kirana (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study aims to describe and analyze education quality management in Islamic boarding schools. This field research used a qualitative approach. Data were collected from two branches of the Islamic boarding school: the Miftahul Khoir Buyat Islamic Boarding School (a branch of the Tebu Ireng Islamic Boarding School) and the Modern Gontor Putri 4 Kendari Islamic Boarding School. Data were obtained by observation, interview, and documentation techniques and analyzed using content analysis techniques. The results of this study indicate that quality planning at Miftahul Khoir Buyat Islamic Boarding School is carried out independently by quality planning analysis. Implementing the quality of education in this pesantren follows the curriculum by guaranteeing the quality of processes, teaching and educational staff as well as facilities and infrastructure. The quality evaluation is carried out periodically with the leadership and external supervision. Whereas quality planning at Pondok Modern Gontor Putri 4 (GP 4) always follows the rules and policies of the planning of the central pesantren. GP 4 has a pesantren curriculum that has been implemented since the beginning and maintained until now; quality evaluation is carried out internally by the branch and central pesantren. The research has implications for equal distribution of quality and management of Islamic boarding schools at the centre and branches. This is important so the quality of pesantren education is maintained.